Muerte de un ciclista = [videorecording (DVD)] : Death of a cyclist - Bardem, Juan Antonio; Bardem, Juan Antonio; Bosé, Lucia, 1931-2020-; Closas, Alberto, 1921-1994; Corra, Bruna (Criterion collection, 2008)
Upper-class geometry professor Juan and his wealthy, married mistress María José, driving back from a late-night rendezvous, accidentally hit a cyclist and run. The resulting tale of guilt, infidelity, and blackmail reveals the wide gap between the rich and the poor in Spain and surveys the corrupt ethics of a society seduced by decadence.